The effects of Chinese botanical lotion and pimecrolimus cream in the treatment of chronic perianal eczema: a randomized clinical trial - Lai, Lixia; Wang, Yanmei; Wen, Luping; Wang, Shaozhao; Chen, Si; Gu, Chao; Zhang, Zeye (Frontiers in Pharmacology, 2025)
BackgroundFumigation and sitz-bath therapy are traditional Chinese medicine (TCM) practices that offer unique benefits for managing chronic perianal eczema (CPE). This study aimed to investigate the clinical efficacy of the traditional Chinese herbal lotion (anal pruritus lotion, APL) combined with pimecrolimus cream in CPE treatment.MethodsPatients with CPE admitted between October 2019 and March 2022 were analyzed. The control group was given basic therapy with pimecrolimus cream, whereas the treatment group received pimecrolimus cream combined with APL under fumigation and sitz-bath therapy. We recorded and compared baseline patient information and clinical symptoms pre- and post-therapy, including clinical symptom scores, the eczema area and severity index (EASI), pruritus visual analogue scale (VAS) scores, dermatology life quality index (DLQI), and efficacy evaluations. Additionally, safety assessments and follow-up surveys were performed, as well.ResultsBaseline data were comparable between the treatment and control groups. Post-therapy, the treatment group exhibited significantly improved outcomes compared to the control group in eczema severity, pruritus VAS scores, and dermatology life quality, with lower relapse rates (P < 0.05). Safety evaluations suggested that the treatments were safe and reliable.ConclusionThe combination of pimecrolimus cream and APL is more effective in the treatment of CPE than pimecrolimus cream alone, providing a promising new approach for the clinical management of perianal eczema.Clinical Trial registrationInternational Traditional Medicine Clinical Trial Registry, http://itmctr.ccebtcm.org.cn/en-US/Home/ProjectView?pid=58f1a168-bdf1-4e2a-a9bd-cf0f4a3ec06f as ITMCTR 2024000576.